NS398 as a potential drug for autosomal‐dominant polycystic kidney disease: Analysis using bioinformatics, and zebrafish and mouse models. Issue 20 (22nd September 2021) - Chen, Sixiu; Huang, Linxi; Zhou, Shoulian; Zhang, Qingzhou; Ruan, Mengna; Fu, Lili; Yang, Bo; Xu, Dechao; Mei, Changlin; Mao, Zhiguo
Abstract: Autosomal‐dominant polycystic kidney disease (ADPKD) is characterized by uncontrolled renal cyst formation, and few treatment options are available. There are many parallels between ADPKD and clear‐cell renal cell carcinoma (ccRCC); however, few studies have addressed the mechanisms linking them. In this study, we aimed to investigate their convergences and divergences based on bioinformatics and explore the potential of compounds commonly used in cancer research to be repurposed for ADPKD. We analysed gene expression datasets of ADPKD and ccRCC to identify the common and disease‐specific differentially expressed genes (DEGs). We then mapped them to the Connectivity Map database to identify small molecular compounds with therapeutic potential. A total of 117 significant DEGs were identified, and enrichment analyses results revealed that they are mainly enriched in arachidonic acid metabolism, p53 signalling pathway and metabolic pathways. In addition, 127 ccRCC‐specific up‐regulated genes were identified as related to the survival of patients with cancer. We focused on the compound NS398 as it targeted DEGs and found that it inhibited the proliferation of Pkd1 −/− and 786‐0 cells. Furthermore, its administration curbed cystogenesis in Pkd2 zebrafish and early‐onset Pkd1 ‐deficient mouse models. In conclusion, NS398 is a potential therapeutic agent for ADPKD.